Genetic Diversity in Marine Planktonic Ciliates (Alveolata, Ciliophora) Suggests Distinct Geographical Patterns – Data From Chinese and European Coastal Waters - Ganser, Maximilian H.; Forster, Dominik; Liu, Weiwei; Lin, Xiaofeng; Stoeck, Thorsten; Agatha, Sabine (Frontiers in Marine Science, 2021)
Unraveling geographic distribution patterns of planktonic protists is a central goal in marine microbial ecology. Using a novel combination of recently developed phylogenetic and network analyses on a V4 18S rDNA metabarcoding dataset, we here analyzed the genetic diversity of marine planktonic ciliate communities in Chinese and European coastal waters. Thereby, our approach provided an unprecedented perspective on geographic patterns inferred from ciliate genetic diversity and accomplished a very fine resolution down to single nucleotides within operational taxonomic units (OTUs). While most OTUs (87%) exclusively contained sequences of either Chinese or European origin, those OTUs detected in both regions comprised the vast majority of reads (84%). Phylogenetic analyses of OTUs belonging to the same taxon revealed genetically distinct clades that were geographically restricted to either Chinese or European coastal waters. The detection of signature nucleotides emphasized this genetic distinction of Chinese and European clades. Second-level clustering of OTUs and reference sequences in two selected taxa (the oligotrichid Spirotontonia and the tintinnid Tintinnidium) revealed the presence of several potentially new species or ones lacking genetic reference data. Geographic patterns were also discovered by network analyses within 700 widespread and abundant OTUs; in 77 of these OTUs, European and Chinese sequences formed significantly assortative groups. These assortative groupings indicated a higher genetic similarity among sequences from the same region than between sequences from different regions. Our results demonstrate that detailed analyses of metabarcoding data down to single nucleotide differences expand our perception of geographical distribution patterns and provide insights into historic and ongoing effective dispersal in protists. The congruent discovery of geographic patterns at different levels of resolution (between and within OTUs) suggests that cosmopolitan distribution in marine planktonic ciliates is less common than previously postulated.